Neuroimaging Findings in Pediatric Patients with Thalassemia Major - Yılmaz Akbaş; Sultan Aydın; Gökçen Öz Tunçer; Alper Köker; Yasemin Çoban; Gönül Oktay; Hakan Yeral (Hematology Reports, 2022)
Background: Cranial magnetic resonance imaging (MRI) studies about iron accumulation in children with thalassemia major are quite limited. Aim: This study aimed to detect neurological findings with cranial MRIs in the pediatric patients with thalassemia major who did not develop any neurological complications. Materials and Methods: Pediatric patients with thalassemia major who followed in the Pediatric Hematology Unit between 1 July 2017 and 1 January 2019 were included in the study. The patients underwent cranial MRI scans. Results: A total of 30 patients were included. The median age was 15 (range from 4–18) years old. We found that 7 patients had a splenectomy and 19 of the remaining 23 patients had splenomegaly. In addition, 13 of the patients had hepatomegaly, 10 had skeletal deformities, and 17 had growth retardation. The mean ferritin level was 3772.3 ± 2524.8. We detected various pathologies on cranial MRI images of 10 (33.3%) patients. In 3 of these patients, millimeter-sized ischemia-compatible lesions were found in the cerebral white matter, which did not fit any arterial area, and 5 patients had hyperintense lesions in the basal ganglia. Conclusion: Our study is valuable since 1/3 of our pediatric patients with thalassemia major were detected with intracranial pathology.